STRATEGI PEMASARAN DAN PENGEMBANGAN PRODUK UMKM UNTUK MENINGKATKAN PENJUALAN PRODUK TRADISIONAL DI PASAR MODERN - Nayla Azizah; Enggy Yose; Hendi Efrianto Harianja; Karyadi Hidayat (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to describe and analyze in depth the product development strategies implemented by Micro, Small, and Medium Enterprises (MSMEs) processing traditional commodities, as well as their impact on increasing sales value and competitiveness in the modern market. Despite their significant intrinsic potential, traditional commodities are often distorted in value due to limitations in packaging, branding, and standardization that do not align with modern market expectations. This study uses a descriptive method with a literature review approach.